ANALISIS PENGARUH EFEKTIVITAS, TRANSPARANSI DAN AKUNTABILITAS PEMERINTAH DESA TERHADAP PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DESA DI KECAMATAN KARTASURA - Rizky Diah Fitriani; Suprihati Suprihati; Maya Widyana Dewi (Jurnal Akuntansi dan Pajak, 2023)
The purpose of this study was to determine the effect of effectiveness, transparency and accountability on the management of the Village Revenue and Expenditure Budget in Kartasura District. The methodology used in this study is a method of quantitative data analysis and testing is carried out using a multiple regression model. The population used in this study were 105 village officials in Kartasura District. In this study, a sample of 95 people was obtained. With a significance value of 0.016 less than α = 0.05, this indicates that the effectiveness variable has a significant effect on the management of the Village Revenue and Expenditure Budget (APBDes). A significant value of 0.018 is less than α = 0.05. This indicates that the transparency variable has a significant effect on the management of the Village Revenue and Expenditure Budget (APBDes). With a significance value of 0.002 less than α = 0.05, this indicates that the accountability variable has a significant effect on the management of the Village Revenue and Expenditure Budget (APBDes). Based on the results of testing the data obtained Fcount of 39.486 greater than Ftable of 2.70 with a significance of 0.000 which is smaller than the significant value α = 0.05 so it can be concluded that simultaneously or together the variables of effectiveness, transparency and accountability are factors that influence variable Village Revenue and Expenditure Budget (APBDes).